2005
DOI: 10.1108/02640470510635782
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of information and communication technology (ICT) in academic libraries

Abstract: PurposeThis study aims to investigate the extent of adoption of information and communication technology (ICT) in university libraries in Nigeria.Design/methodology/approachPostal survey was the instrument used for data collection. Almost 60 per cent of the University Librarians out of the 29 university libraries surveyed completed their questionnaires.FindingsThe results of the survey show that only six university libraries are fully “computerized”, nine are “about to be computerized”; seven of the surveyed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 6 publications
2
26
0
Order By: Relevance
“…The findings of this paper agree with those of (Ani, Esin, & Edem, 2005) who found an association between vice chancellors attitude towards ICTs, and ICT adoption in their respective libraries. Ani et Al., (2005) further suggested that national wide seminars and workshops for all vice chancellors to address their attitude on ICTs to make them give way to positive ones that enhance rapid adoption of ICT in their university libraries. From the results of this paper, we can therefore generalize that Vice chancellors characteristic related to ICTs influence academic staff to adopt and diffuse LMS in their teaching and learning.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of this paper agree with those of (Ani, Esin, & Edem, 2005) who found an association between vice chancellors attitude towards ICTs, and ICT adoption in their respective libraries. Ani et Al., (2005) further suggested that national wide seminars and workshops for all vice chancellors to address their attitude on ICTs to make them give way to positive ones that enhance rapid adoption of ICT in their university libraries. From the results of this paper, we can therefore generalize that Vice chancellors characteristic related to ICTs influence academic staff to adopt and diffuse LMS in their teaching and learning.…”
Section: Discussionsupporting
confidence: 91%
“…Information and communication technology which offers fast and increased alternatives to information resource gathering and research orientation bringing about accuracy and efficiency in university libraries and the entire library environment. This development as observed by Ani, Esin and Edem (2005) has created a shift from traditional information environment to electronic environment such as computer use, internet use, online services as well as online databases to library operations. The emergence of ICTs and other digital technologies and networks has dramatically brought innovations in librarianship.…”
Section: Librarians Now Perform Their Library Operations Utilizingmentioning
confidence: 99%
“…Omoniwa (2001) traced the attempt to computerize Kashim Ibrahim Library at Ahmadu Bello University (ABU), Zaria, Kaduna state from 1972 to 2001 and discussed the problems that had militated against the computerization effort. Ani, Esin and Edem (2006) surveyed the adoption of ICT in Nigerian academic libraries and reported that only six libraries are fully computerized as at that time. Oketunji, Daniel, Okojie and Abdulsalam (2012) in their study were concerned with determining the state and future of ICT in libraries and information services in Nigeria.…”
Section: Justification/significance Of the Studymentioning
confidence: 99%